2014
DOI: 10.2190/ic.34.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Tendencies of High and Low Barrier Personalities in Narratives of Everyday and Dream Memories

Abstract: The use of computerized content analysis has encouraged great interest in the assessment of personality. Given the psychological importance of body boundaries in the maintenance and regulation of the self, this study aimed to assess the lexical tendencies of High and Low Barrier personalities (Fisher & Cleveland, 1956, 1958), as measured using the BTD (Wilson, 2006), with regard to lexical frequencies, as classified by the Linguistic Inquiry and Word Count (LIWC) (Pennebaker, Booth, & Francis, 2007). Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As heightened levels of primordial mental activity have been associated with an increase in use of metaphorical language (Freud, 1900), this study also aims to explore how High and Low Barrier personalities use metaphorical expressions differently in narratives of everyday memories and of dream memories. In particular, previous literature has identified that Low Barrier personalities showed more frequent instances of expressing their thoughts and emotions directly, whereas High Barrier personalities communicated their emotions and thoughts less often (Cariola, 2015). From this context, it is possible to infer that High Barrier personalities communicate their thoughts and emotions through the use of metaphorical expressions more frequently than Low Barrier personalities.…”
Section: Aims Of This Studymentioning
confidence: 79%
See 3 more Smart Citations
“…As heightened levels of primordial mental activity have been associated with an increase in use of metaphorical language (Freud, 1900), this study also aims to explore how High and Low Barrier personalities use metaphorical expressions differently in narratives of everyday memories and of dream memories. In particular, previous literature has identified that Low Barrier personalities showed more frequent instances of expressing their thoughts and emotions directly, whereas High Barrier personalities communicated their emotions and thoughts less often (Cariola, 2015). From this context, it is possible to infer that High Barrier personalities communicate their thoughts and emotions through the use of metaphorical expressions more frequently than Low Barrier personalities.…”
Section: Aims Of This Studymentioning
confidence: 79%
“…Kinship represents a group entity that is defined by its emotional attachments and shared genetics; thus, this entity is differentiated from other social groups and relationships. In this context, the high frequency of references to kinship echoes the High Barriers' tendency to emphasise group membership (Cariola, 2015). Kinship has also been anthropologically associated with nurturing and protection against individuals who are not kin (Murphy, 2008).…”
Section: H2mentioning
confidence: 99%
See 2 more Smart Citations
“…Given the theoretical relationship that relates an inflation of penetration imagery to higher levels of primordial thought functioning, empirical research has shown that the frequencies of penetration imagery correlate positively with primordial thought language in various types of religious texts (Cariola, 2012a, 2012b; Wilson, 2009). Empirical research has demonstrated that both penetration and barrier imagery increase with the level of regressive cognition, which indicates that barrier and penetration imagery reflects the different psychological functions of phenomena related to regressive cognition (Cariola, 2013; see also Cariola, in press). Primordial thought language has been measured using the Regressive Imagery Dictionary (RID; Martindale, 1975, 1990), which gauges the frequency of lexical items classified as primordial thought language and conceptual thought language.…”
Section: Introductionmentioning
confidence: 99%